Organizing The Subject of The Spectral Series of The Hydrogen Atom on The Base of New Pedagogical Technologies (Pedagogical Cluster-Journal of Pedagogical Developments, 2023)
This article talks about teaching the topics of Bohr's postulates, spectral series in the hydrogen atom, Balmer's formula, Balmer's generalized formula, Rydberg-Ritz's combinatorial principle based on modern pedagogical technologies.